'I'm coming back again!' The resilience process of early career teachers - Mansfield, C.; Beltman, Susan; Price, A. (Carafax Publishing, Taylor and Francis Group, 2014)
Early career teachers face a range of challenges in their first years of teaching and how these challenges are managed as career implications. Based on current literature, this paper presents a model of early career teacher resilience where resilience is seen as a process located at the interface of personal and contextual challenges and resources. Through a semi-structured interview the challenges faced by 13 Australian early career teachers and the resources available to manage these challenges are examined. Findings show that beginning teachers experience multiple, varied and ongoing challenges and that personal and contextual resources are both importing in sustaining them through the beginning year(s) of their teaching careers. The study emphasises the critical roles played by family and friends and the importance of relationships in the resilience process. Implications for future research and teacher education are discussed.